Effects of plant density on cotton yield components and quality - Xiao-yu ZHI; Ying-chun HAN; Ya-bing LI; Guo-ping WANG; Wen-li DU; Xiao-xin LI; Shu-chun MAO; Lu FENG (Journal of Integrative Agriculture)
Yield and fiber quality of cotton even varies within locules in a boll, but it is not clear how yield components and quality parameters are altered across seed positions of a locule (SPL). A field experiment was arranged in a split plot design with transgenic insect resistant Bt (Bacillus thuringiensis) cotton hybrid cultivar CRI75 and conventional cultivar SCRC28 as the main plots, and three plant densities (15 000, 51 000 and 87 000 plants ha−1) as the subplots in 2012 and 2013 at Anyang, Henan Province, China. Cotton was hand harvested by node and fruiting position, and then seeds of the first fruiting position bolls from nodes 6–10 were separated by SPL. The effects of plant density on lint yield, fiber quality, especially across SPL were determined. It was showed that plant densities of 51 000 and 87 000 plants ha−1 increased lint yield by 61.3 and 65.3% in 2012 and 17.8 and 15.5% in 2013 relative to low plant density (15 000 plants ha−1), however, no significant difference was observed between 51 000 and 87 000 plants ha−1. The number of bolls (boll density) increased while boll weight decreased as plant density raised, and no significant changes occured in lint percentage in 2013 but increased with plant density in 2012. The number of bolls in upper nodes and distal fruiting positions, the number of seeds per boll, seed area (SA) and seed vigor index increased with decreasing plant density. Seed area was found to be greater from the base to the middle compared to the apex of a locule. Mote frequency (MF) increased as plant density increased, and fiber quality was the best at the middle of the locule regardless of plant density. As the number of fibers per seed area is genetically determined, adjusting plant density to produce more seeds and greater seed area can be a potentially promising alternative to improve lint yield in cotton. These findings might be of great importantance to cotton breeding and filed management.